The ombudsman in the modern state - Stuhmcke, Anita; Groves, Matthew (London [England] : Hart Publishing, 2022)
"Ombudsmen are a global phenomenon. They are also a critical part of the public law frameworks of modern liberal democracies. This is the first edited collection to examine the place of the ombudsman in the modern state. It brings together key international scholars to discuss current and future challenges for the Ombudsman institution and the systems of government within which they operate. The book is international in scope with authors heralding from most continents - Canada, the Netherlands, the United Kingdom, Australia, New Zealand, Hong Kong, South Africa, Germany, and Austria. This global analysis is both in-depth and expansive in its coverage of the operation of Ombudsmen across civil and common law legal systems. The book has two key themes: - The enduring question of the location and operation of Ombudsmen within public law systems in a changing state, and - The challenges faced by Ombudsmen in contemporary governance. This collection adds to the public law scholarship by addressing a common problem faced by all avenues of public law review - the evolving nature of modern public administration."--
1. The Evolution of the Ombudsman Anita Stuhmcke (University of Technology Sydney, Australia) and Matthew Groves (Deakin University, Australia) Part 1 ? The Place of the Ombudsman in Modern Governance -- 2. Maladministration: The Particular Jurisdiction of the Ombudsman Greg Weeks (Australian National University, Australia) -- 3. What Is, and What Should Be, the Relationship Between Ombudsman Remedies and Judicial Review? Stephen Thomson (City University of Hong Kong) -- 4. The Ombudsman Role in System Improvement: A Conceptual Mode Gavin McBurnie (Queen Margaret University, UK) -- 5. The Role of Ombuds Institutes in Providing Equal Access to Justice For All Maaike de Langen (New York University, Center on International Cooperation. -- 6. The Implications for Ombudsman of Fundamental Changes in the Environment in Which They Operate Chris Wheeler (University of Technology Sydney, Australia) -- 7. Ombuds and Tribunals in a Digital Era Naomi Creutzfeldt (University of Westminster, UK) Part 2 ? The Challenge of Modern Governance to Ombudsmen -- 8. Complaint Handling Effectiveness ? What Can We Learn from Industry Ombudsmen? John McMillan (Australian National University, Australia) -- 9. Managing Accountability and Reputation in the Complex Constitution: A Study into the UK Ombudsman Sector Richard Kirkham (University of Sheffield, UK) -- 10. Engagement with Service Users Rob Behrens (Parliamentary and Health Services Ombudsman, UK) -- 11. Ombudsman and Counter-Democracy: Gas Quakes in the Netherlands and the Democratic Role of the National Ombudsman Marc Hertogh (University of Groningen, the Netherlands) -- 12. Towards Therapeutic Complains Resolution Chris Gill (University of Glasgow, UK), Carolyn Hirst (Hirstworks, UK) and Jane Williams (Queen Margaret University, UK) -- 13. High Official at Street-Level: A Multi-Method Study on the Effects of Consultation Days with the Austrian Ombudsperson Axel Pohn-Weidinger (University of Gèottingen, Germany) and Julia Dahlvik (University of Applied Sciences FH Campus Wien, Austria) -- 14. Reimagining Administrative Justice Justice Nick O'Brien (Mental Health Review Tribunal, UK) -- 15. A Guardian Illuminated: The Role of New Zealand's Parliamentary Ombudsman in the Health and Disability System Ron Paterson (University of Auckland, New Zealand) -- 16. Ombuds Institutions: Protection and Promotion of the Rights of Older Persons Linda Reif (University of Alberta, Canada)
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Ombudspersons; Electronic books